Safety and tolerability of silk fibroin hydrogels implanted into the mouse brain. (November 2016) - Fernández-García, Laura; Marí-Buyé, Núria; Barios, Juan A.; Madurga, Rodrigo; Elices, Manuel; Pérez-Rigueiro, José; Ramos, Milagros; Guinea, Gustavo V.; González-Nieto, Daniel
Graphical abstract: Abstract: At present, effective therapies to repair the central nervous system do not exist. Biomaterials might represent a new frontier for the development of neurorestorative therapies after brain injury and degeneration. In this study, an in situ gelling silk fibroin hydrogel was developed via the sonication-induced gelation of regenerated silk fibroin solutions. An adequate timeframe for the integration of the biomaterial into the brain tissue was obtained by controlling the intensity and time of sonication. After the intrastriatal injection of silk fibroin the inflammation and cell death in the implantation area were transient. We did not detect considerable cognitive or sensorimotor deficits, either as examined by different behavioral tests or an electrophysiological analysis. The sleep and wakefulness states studied by chronic electroencephalogram recordings and the fitness of thalamocortical projections and the somatosensory cortex explored by evoked potentials were in the range of normality. The methodology used in this study might serve to assess the biological safety of other biomaterials implanted into the rodent brain. Our study highlights the biocompatibility of native silk with brain tissue and extends the current dogma of the innocuousness of this biomaterial for therapeutic applications, which has repercussion in regenerative neuroscience. Statement of Significance: The increasingly use of sophisticated biomaterials to encapsulate stem cells has changed the comprehensive overview of potential strategies for repairing the nervous system. Silk fibroin (SF) meets with most of the standards of a biomaterial suitable to enhance stem cell survival and function. However, a proof-of-principle of the in vivo safety and tolerability of SF implanted into the brain tissue is needed. In this study we have examined the tissue bioresponse and brain function after implantation of SF hydrogels. We have demonstrated the benign coexistence of silk with the complex neuronal circuitry that governs sensorimotor coordination and mechanisms such as learning and memory. Our results have repercussion in the development of advances strategies using this biomaterial in regenerative neuroscience.